Deleterious effects of polypropylene released from paper cups on blood profile and liver tissue of Clarias gariepinus: bioremediation using Spirulina - Eid, Zainab; Mahmoud, Usama M.; Sayed, Alaa El-Din H. (Frontiers in Physiology, 2024)
Despite numerous studies on microplastics, the biological impacts of polypropylene microplastics (PP-MPs) and its toxicity on freshwater fish have yet to be fully revealed. The purpose of this research was to look at the potentially harmful effects of PP-MPs in freshwater African catfish Clarias gariepinus and bioremediation using Spirulina. After acclimatization to laboratory conditions, 108 fish (125 ± 3 gm and 27 ± 2 cm) were assigned into triplicate six experimental groups (12 fish/group), a control group, Spirulina group (SP), PP-MP-treated groups (0.14 and 0.28 mg/l PP-MPs), and PP-MP + Spirulina-treated groups (0.14 mg/l PP-MPs + 200 mg/L SP and 0.28 mg/l PP-MPs +200 mg/L SP) for 15-day exposure and 45-day recovery after that. The hematological parameters exhibiting significance (RBCs, Hct, Hb, and MCV) or non-significance (MCH and MCHC) either decreased with the increase in PP-MP doses from 0.0 in the control to 0.28 mg/L red blood cells (RBCs), hematocrit (Hct), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), hemoglobin (Hb) and platelets or increased with such an increase in doses (mean corpuscular volume (MCV)). The liver enzyme activity, aspartate aminotransferase (AST), alkaline phosphatase (ALP), and alanine aminotransferase (ALT) exhibited non-significant (p ≥ 0.05) or significant (p < 0.05) increases in (0.14 and 0.28 mg/L) PP-MP-exposed groups, respectively, except ALP. Furthermore, there was a significant (p < 0.05) or non-significant (p ≥ 0.05) increase in 0.14 and 0.28 mg/l PP-MP +200 mg/L-exposure groups, respectively, compared to the control group and the same exposure group without Spirulina. In comparison to the control group, PP-MPs (0.14 and 0.28 mg/L) induced a significant (p < 0.05) increase in the percentage of poikilocytosis and nuclear abnormalities of RBCs. The liver tissue from fish exposed to PP-MPs exhibited varying degrees of pathological changes. These results indicated that these pathological changes increased with PP-MP concentration, suggesting that the effect of PP-MPs was dose-dependent. After 45 days of recovery under normal conditions, it was obvious that there was a significant improvement in the percentage of poikilocytosis and nuclear abnormalities of RBCs, as well as a non-significant improvement in hemato-biochemical parameters and liver tissue.